PENDIDIKAN KARAKTER SEBAGAI SARANA PEMBANGUNAN NILAI KERENDAHAN HATI DAN NILAI TOLERANSI TINJAUAN AL-QURAN - Zulkarnain Zulkarnain (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2017)
Through character education, it is hoped that the nation’s children can the social interactions in people who have diverse backgrounds that vary and ability of the entrepreneur, Attitudes to understand the differences appreciate the differences and be able to survive in life through the skill and the emergence of diversity of views when put together can be trans- is alienatedfr om its own cultural values and ignorant about the charac- In this context, as a nation would not be willing ifthe  younger generation future generations of the importance of character education as a means teristics of its people. One effort to build awareness and understanding of building the value of humility and tolerance values always uphold in formed into a common moralfor ce that becomes extraordinary energy to realize the progress of the nation. The goal is to shape the personality of the child, in order to be a good human being, a good citizen, and a good citizen. In implicating one’s humble value must be colored with the value of truth and reject the trait of the pervert in the sense of abandoning his pride. The inferior individual realizes that whatever he has. Then inculcate each individual life tolerance values diversity always respect the identity, And the uniqueness of each religion, neither discriminating nor eliminating it, Either through religious conversion or confusion of reli- gious rituals that are expected to be a responsible and democratic citizen.